Structural and physical properties of trichloroethylene under an external electric field. (4th August 2021) - Tao, Yaping; Su, Mingzhu; Duan, Zhixia; Han, Ligang; Sun, Kexi
Abstract: Study on a series of physical and chemical changes of molecules under an external electric field (EEF) can deeply understand the properties of molecules. Trichloroethylene is widely used in industrial solvents, extractants, fungicides, refrigerants, dry cleaning, and other fields. In this work, the structural and physical characteristics of trichloroethylene under EEF were investigated on the basis of density functional theory within the B3LYP/def2‐TZVP level. Calculated results show that the bond lengths, bond angles, total energy, dipole moment, charge, and Raman spectra change under EEF. Under the effect of EEF, the Raman spectra show vibrational stark effect, which causes a redshift or blueshift of the wavenumbers. These results help to understand the effect of EEF on structures and physical properties and provide effective guidance for various applications. Abstract : In this study, a series of physical and chemical changes of molecules under an external electric field (EEF) is investigated and describes the effect of EEF on the geometric parameters, total energy, dipole moment, change, electron density difference, energy level distribution, ADCH charge, Raman spectra, dissociation properties, gap, and so on.